Coming off fossil fuels: Visual recollection of fossil fuel dependency. Issue 3 (27th May 2022) - Uusitalo, Niina
Abstract : As participants of the global capitalist system, we have rich and lifelong experiences of living with fossil fuels. However, these experiences are often implicit in our everyday lives, and rarely formulated explicitly. Coming off Fossil Fuels is a project that visualises and collects personal experiences of fossil fuel dependencies. Experiences can include memories, current attachments and future dreams connected to fossil fuels. This article is a methodological account of collecting fossil fuel experiences through two modes of visual recollection: (1) an autobiographical video piece visualising the author's own dependencies on fossil fuels and (2) gallery visitors' fossil fuel experiences. The article utilises a participatory arts-based approach in which gallery visitors were able to react to the video in recorded responses. The video was presented as part of the 2022 LOOK Climate Lab thinking space in Open Eye Gallery, Liverpool, where video responses were collected. The article also discusses possibilities for developing a method of visual recollection by considering temporal and spatial dimensions of fossil fuel dependency.